Father Involvement as A Parent Figure In Children's Cognitive Development - Nur Afifah (HMPS PIAUD FTIK IAIN Jember, 2022)
Father involvement in parenting is the father's positive participation in activities in the form of direct interaction with his child, providing warmth, supervising and controlling the child's activities, and being responsible for the child's needs. Fathers are equal parenting partners, meaning they have the same rights and responsibilities as mothers. Fathers have different characteristics from mothers. It means that fathers also have an essential role in the growth and development, and formation of positive characters in children that mothers may not obtain. The father's role will increase children's intelligence and social-emotional, motor, and cognitive abilities. Cognitive development is vital in children's learning success because most learning activities are always related to problems with remembering and thinking. Children will learn from parents about the ability to solve problems and recognize problems in children as a figure that shows the formation of behavior, including exemplary, conditioning, and insight. ABSTRAK Father Involvement/keterlibatan ayah dalam pengasuhan adalah partisipasi positif ayah dalam kegiatan berupa interaksi langsung dengan anaknya, memberikan kehangatan, mengawasi dan mengontrol kegiatan anak, serta bertanggung jawab atas kebutuhan anak. Ayah adalah mitra setara dalam pengasuhan anak, yang berarti mereka memiliki hak dan tanggung jawab yang sama sebagai ibu. Ayah memiliki karakteristik yang berbeda dengan ibu. Artinya ayah juga memiliki peran penting dalam pertumbuhan dan perkembangan serta pembentukan karakter positif pada anak yang mungkin tidak didapatkan dari ibu. Peran ayah akan meningkatkan perkembangan kecerdasan, sosial emosional, motorik dan kemampuan kognitif pada anak. Perkembangan kognitif mempunyai peranan penting bagi keberhasilan anak dalam belajar, karena sebagian besar aktivitas dalam belajar selalu berhubungan dengan masalah mengingat dan berfikir.anak akan belajar dari orangtua tentang kemampuan memecahkan masalah dan mengenali masalah pada diri anak, Dalam kaitannya dengan pengembangan diri anak, orang tua sebagai figur yang menunjukkan pembentukan perilaku meliputi keteladanan, pengkondisian, dan wawasan.